Nutraceuticals in HIV and COVID-19-Related Neurological Complications: Opportunity to Use Extracellular Vesicles as Drug Delivery Modality - Sunitha Kodidela; Sandip Godse; Asit Kumar; Xuyen H. Nguyen; Alina Cernasev; Lina Zhou; Ajay Kumar Singh; Hari K. Bhat; Santosh Kumar (Biology, 2022)
People living with HIV/AIDS (PLWHA) are at an increased risk of severe and critical COVID-19 infection. There is a steady increase in neurological complications associated with COVID-19 infection, exacerbating HIV-associated neurocognitive disorders (HAND) in PLWHA. Nutraceuticals, such as phytochemicals from medicinal plants and dietary supplements, have been used as adjunct therapies for many disease conditions, including viral infections. Appropriate use of these adjunct therapies with antiviral proprieties may be beneficial in treating and/or prophylaxis of neurological complications associated with these co-infections. However, most of these nutraceuticals have poor bioavailability and cannot cross the blood–brain barrier (BBB). To overcome this challenge, extracellular vesicles (EVs), biological nanovesicles, can be used. Due to their intrinsic features of biocompatibility, stability, and their ability to cross BBB, as well as inherent homing capabilities, EVs hold immense promise for therapeutic drug delivery to the brain. Therefore, in this review, we summarize the potential role of different nutraceuticals in reducing HIV- and COVID-19-associated neurological complications and the use of EVs as nutraceutical/drug delivery vehicles to treat HIV, COVID-19, and other brain disorders.